DAGESTAN PROFESSIONAL MUSICAL ART IN HISTORICAL DEVELOPMENT: THE SECOND HALF OF THE XX - BEGINNING OF THE XXI CENTURY - Abdullaeva, El'mira Basirovna (History, Archeology and Ethnography of the Caucasus, 2021)
The article describes the patterns and features of the development of the musical art of Dagestan at different stages of its evolution over more than half a century of history. We have analyzed the components of the musical and professional tradition, giving a holistic view of it, versatile reflecting both the originality and originality, and historical variability. These include: genre-species differentiation and systemic connections, stylistics and means of musical expression. The multifaceted study and the possibility of interpreting the data obtained allows one to create an idea of ​​the ways of the formation and development of the musical art of Dagestan during the period under consideration. The initial premises of the study can be summarized as follows. The structure of musical art is formed on the basis of the interrelationships of composer’s creativity, performing practice and various cultural interchanges that undergo stylistic and genre-specific changes. The second premise was the look at the musical art of Dagestan as an actual part of modern culture. Therefore, the main source has become various forms of broadcasting musical culture (listening practice and analytical observations at concerts of classical music). Reliance on contemporary musical material and direct observation of the musical process in the field of classical, pop and other spheres of culture presupposes the study of the phenomenon in a synchronic aspect. The presence of publications by different authors and our own research experience make it possible to a certain extent to make diachronic comparisons. The important regularities in the development of the Dagestan academic musical art identified by us can form the basis for further research of genre phenomena in different historical periods.